2018
DOI: 10.1016/j.jpainsymman.2018.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Communication and Trust in Patients With Serious Illness: An Exploratory Study of the Relationships of Race/Ethnicity, Socioeconomic Status, and Religiosity

Abstract: Contrary to prior studies, racial/ethnic minorities and patients with lower income rated communication higher and reported higher trust in their clinicians than white and higher income patients. More research is needed to identify and understand factors associated with quality communication and trust between seriously ill patients and clinicians to guide development of patient-centered palliative care communication interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 40 publications
1
21
0
1
Order By: Relevance
“…A limited number of studies have found that race and ethnicity influence PPR, for example, patient-centered encounters, communication ratings, and trust in the provider, but confounding factors can lead to conflicting study results. 57,58 More research on race and ethnicity is needed.…”
Section: During Office Hoursmentioning
confidence: 99%
“…A limited number of studies have found that race and ethnicity influence PPR, for example, patient-centered encounters, communication ratings, and trust in the provider, but confounding factors can lead to conflicting study results. 57,58 More research on race and ethnicity is needed.…”
Section: During Office Hoursmentioning
confidence: 99%
“…However, most of the elements of support and communication measured by this instrument were associated with a significant change in PTSD symptoms even after adjusting for patient death in a multivariable model, suggesting that this content is applicable to both bereaved and non-bereaved surrogates. Additionally, the results of the ADBFMI are generally interpreted using composite problem scores rather than responses to each individual question, and our utilization of both represents a different approach that has recent precedent in the medical literature [35]. As such, results for analyses of specific items should be considered exploratory in nature.…”
Section: Discussionmentioning
confidence: 99%
“…15 However, other studies failed to show a clear disparity in patient-reported QOC. 16,17 In fact, Coats et al 17 showed increased satisfaction with communication among racial and ethnic minorities and those of lower socioeconomic status in a study of enhanced communication in serious illness in the outpatient setting. Measures of satisfaction with communication for seriously ill patients in the acute care setting, particularly in the intensive care unit (ICU), have not been compared by race or ethnicity.…”
Section: Introductionmentioning
confidence: 99%